For richer or poorer: income and wealth in New Zealand (Wellington, New Zealand : New Zealand Planning Council, 1988)
This report outlines the findings of the study is to describe, within the limits of the data available, the distribution of income and wealth in New Zealand.
The first report of the Income Distribution Group
aia 13/02/2019
Loans
Keywords: Consumption (Economics); Supply and demand; Price maintenance